Mesenchymal stem cell-derived exosomes as a promising cell-free therapy for knee osteoarthritis - Luo, Danni; Zhu, Hao; Li, Song; Wang, Zhenggang; Xiao, Jun (Frontiers in Bioengineering and Biotechnology, 2024)
Osteoarthritis (OA), as a degenerative disease, leads to high socioeconomic burdens and disability rates. The knee joint is typically the most affected and is characterized by progressive destruction of articular cartilage, subchondral bone remodeling, osteophyte formation and synovial inflammation.The current management of OA mainly focuses on symptomatic relief and does not help to slow down the advancement of disease. Recently, mesenchymal stem cells (MSCs) and their exosomes have garnered significant attention in regenerative therapy and tissue engineering areas. Preclinical studies have demonstrated that MSC-derived exosomes (MSC-Exos), as bioactive factor carriers, have promising results in cell-free therapy of OA. This study reviewed the application of various MSC-Exos for the OA treatment, along with exploring the potential underlying mechanisms. Moreover, current strategies and future perspectives for the utilization of engineered MSC-Exos, alongside their associated challenges, were also discussed.